Designing a Café Marketing Information System Using a Prototype Café Website for Banua Coffee Café in Makassar - Azisyah, Nur Ilmi; Saleh, Anis; Hafid, Muh Fachri (Journal of Sustainability Industrial Engineering and Management System, 2023)
Makassar, located in South Sulawesi, is home to numerous Micro, Small, and Medium-sized Enterprises (UMKM) spanning various industries, including fashion, culinary, retail, cafes, and more. This diversity contributes significantly to the local economy, especially in South Sulawesi. According to data provided by the Ministry of Micro, Small, and Medium-sized Enterprises of South Sulawesi, there are 206 café operators, 515 coffee shops, and 37 local eateries registered in the city of Makassar. One such establishment is Café Banua Coffee, situated at Jl. Biring Romang Lorong 6 No.12, Tamalanrea, Makassar.This research aims to design a promotional medium in the form of a café website that caters to consumer preferences. This study involves the development of a design strategy and the implementation of an information system through the creation of a Prototype Café Website. The goal is to introduce the café's profile engagingly, providing users with insights into the café's ambiance, facilities, menu offerings, and other relevant information about Café Banua. Data collection is conducted quantitatively using a questionnaire. Respondents' information is categorized by name, age, occupation, and prior knowledge of the café before visiting. Based on the questionnaire data collected, it is evident that the majority of respondents place high importance on the desired features and user comfort in the Prototype Information System Design for Café Banua Coffee's Website.